The empire of civilization : the evolution of an imperial idea - Bowden, Brett, 1968- (University of Chicago Press, 2009)
"Brett Bowden examines how the idea of civilization has informed our thinking about more than ten centuries of global encounters among the different peoples of our world." "From the Crusades to the colonial era to the global war on terror, this volume exposes "civilization" as a stage-managed account of history that legitimizes imperialism, uniformity, and conformity to Western standards, culminating in a liberal-democratic global order. Along the way, Bowden explores the variety of confrontations and conquests - as well as those peoples and places excluded or swept aside - undertaken in the name of civilization. Concluding that the "West and the rest" have more commonalities than differences, this provocative and engaging book ultimately points the way toward an authentic intercivilizational dialogue that emphasizes cooperation over clashes."--Jacket